Bowel Lengthening Procedures in Children with Short Bowel Syndrome: A Systematic Review - Nagelkerke, Sjoerd C. J.; Poelgeest, M. Y. van; Wessel, L. M.; Mutanen, A.; Langeveld, H. R.; Hill, S.; Benninga, M. A.; Tabbers, M. M.; Bakx, R.; on behalf of the ERNICA Intestinal Failure Working Group (European Journal of Pediatric Surgery, 2021)
Introduction The aims of the study are to systematically assess and critically appraise the evidence concerning two surgical techniques to lengthen the bowel in children with short bowel syndrome (SBS), namely, the longitudinal intestinal lengthening and tailoring (LILT) and serial transverse enteroplasty (STEP), and to identify patient characteristics associated with a favorable outcome.Materials and Methods MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) databases were searched from inception till December 2019. No language restriction was used.Results In all, 2,390 articles were found, of which 40 were included, discussing 782 patients. The median age of the patients at the primary bowel lengthening procedure was 16 months (range: 1–84 months). Meta-analysis could not be performed due to the incomparability of the groups, due to heterogeneous definitions and outcome reporting. After STEP, 46% of patients weaned off parenteral nutrition (PN) versus 52% after LILT. Mortality was 7% for STEP and 26% for LILT. Patient characteristics predictive for success (weaning or survival) were discussed in nine studies showing differing results. Quality of reporting was considered poor to fair.Conclusion LILT and STEP are both valuable treatment strategies used in the management of pediatric SBS. However, currently it is not possible to advise surgeons on accurate patient selection and to predict the result of either intervention. Homogenous, prospective, outcome reporting is necessary, for which an international network is needed.
Keywords: longitudinal intestinal lengthening and tailoring; Bianchi; serial transverse enteroplasty; pediatric; intestinal failure